PENGGUNAAN WEB UNTUK MENINGKATKAN KUALITAS KERJA PEGAWAIPADA PEMERINTAH DAERAH KABUPATEN TANGERANG - Ulis Bella; Ruli Supriati (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2016)
Technological current developments more rapidly, many users to improve of information technology the way of delivering information in various ways, one of them with the website. in technology advances especially in the field of information and communication has encouraged globalization in the office and the more it needs new information, where the information is easy in the can by using web technology, namely the Internet, where information needs to be better in terms of speed, capacity and sophistication in providing information. Many people have realized that the web is not just a mere web page, but also can interact with visitors. The web has become a user interface for database applications, and Web information systems have become scattered, nowadays almost anyone can do accessing information over the web. As well as the Tangerang District Government will improve system performance through running. Likewise in the warehouse that is not computerized Web -based, but still using Microsoft excel, so that the warehouse often experience difficulties and delays in processing the data and create reports . With the web-based goods inventory system, is expected to help users interested in parts warehouse Revenue Office Tangerang District Government, and effectiveness in many ways.